Laberiini, a new tribe of Tropiduchidae planthoppers from Madagascar (Hemiptera: Fulgoroidea) - Stroiński, Adam; Bourgoin, Thierry; Szwedo, Jacek (European Journal of Taxonomy, 2022)
The tropiduchid monotypic genus Laberia Stål, 1866, endemic to Madagascar, is placed in a new tribe of its own Laberiini trib. nov. The tribe is placed in the subfamily Elicinae, and can be distinguished from other representatives of the subfamily by the unique combination of morphological characters of the head, tegmina, legs and genital structures. The genus Laberia and its only species Laberia palliata Stål, 1866 are redescribed, chresonymy is presented and nomenclatorial questions are clarified. Distributional data from Madagascar and doubtful presence of the taxon in Mauritius are discussed. Taxonomic content of Elicinae is briefly discussed.